2021
DOI: 10.15252/emmm.202012461
|View full text |Cite
|
Sign up to set email alerts
|

Combination therapies induce cancer cell death through the integrated stress response and disturbed pyrimidine metabolism

Abstract: By accentuating drug efficacy and impeding resistance mechanisms, combinatorial, multi‐agent therapies have emerged as key approaches in the treatment of complex diseases, most notably cancer. Using high‐throughput drug screens, we uncovered distinct metabolic vulnerabilities and thereby identified drug combinations synergistically causing a starvation‐like lethal catabolic response in tumor cells from different cancer entities. Domperidone, a dopamine receptor antagonist, as well as several tricyclic antidepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
(54 reference statements)
0
7
0
Order By: Relevance
“…The combination of mitochondrial uncoupler niclosamide ethanolamine and dopamine receptor antagonist domperidone or TCAs induces ISR and leas to apoptosis in multiple cancer cell lines including CRC, GBM (Glioblastoma multiforme) and PDAC (Pancreatic ductal adenocarcinoma) cell lines (Hartleben et al, 2021). Even without inducing apoptosis, the ISR is induced by ONC201 in cancer cells exhibiting decreased cell proliferation (Kline et al, 2016).…”
Section: Dual Roles Of the Integrated Stress Response In Cancermentioning
confidence: 99%
“…The combination of mitochondrial uncoupler niclosamide ethanolamine and dopamine receptor antagonist domperidone or TCAs induces ISR and leas to apoptosis in multiple cancer cell lines including CRC, GBM (Glioblastoma multiforme) and PDAC (Pancreatic ductal adenocarcinoma) cell lines (Hartleben et al, 2021). Even without inducing apoptosis, the ISR is induced by ONC201 in cancer cells exhibiting decreased cell proliferation (Kline et al, 2016).…”
Section: Dual Roles Of the Integrated Stress Response In Cancermentioning
confidence: 99%
“…Intriguingly, DDIT4 (induced by metformin, p53, and p63) can form a complex with TXNIP to trigger cell death under oxidative stress [ 46 , 47 ]. UPP1 is a pyrimidine degrading enzyme that contributes to cancer cell death in response to drugs that induce lethal catabolic stress [ 48 ]. Finally, GADD34 is a pro-apoptotic gene induced by DNA damage, and is also regulated by ATF3 [ 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cancer is believed to exhibite a fundamental trait of metabolic rewiring. Malignant cells alter their metabolic pathways in response to various intrinsic and extrinsic challenges to fuel cell survival and expansion ( 28 ). A vast body of evidence has shown that PyM failure is closely associated with cancer growth, and various medications targeting PyM have been authorized for a variety of cancers.…”
Section: Discussionmentioning
confidence: 99%